Manifesto for Living in the Anthropocene - Gibson, Katherine; Rose, Deborah Bird; Fincher, Ruth (punctum books, 2015)
The recent 10,000 year history of climatic stability on Earth that enabled the rise of agriculture and domestication, the growth of cities, numerous technological revolutions, and the emergence of modernity is now over. We accept that in the latest phase of this era, modernity is unmaking the stability that enabled its emergence. Over the 21st century severe and numerous weather disasters, scarcity of key resources, major changes in environments, enormous rates of extinction, and other forces that threaten life are set to increase. But we are deeply worried that current responses to these challenges are focused on market-driven solutions and thus have the potential to further endanger our collective commons. Today public debate is polarized. On one hand we are confronted with the immobilizing effects of knowing "the facts" about climate change. On the other we see a powerful will to ignorance and the effects of a pernicious collaboration between climate change skeptics and industry stakeholders. Clearly, to us, the current crisis calls for new ways of thinking and producing knowledge. Our collective inclination has been to go on in an experimental and exploratory mode, in which we refuse to foreclose on options or jump too quickly to "solutions."